How children succeed confidence, curiosity and the hidden power of character - Paul Tough (London Arrow Books, 2014)
Why do some children succeed while others fail? The story we usually tell about childhood and success is the one about intelligence: success comes to those who score highest on tests, from preschool admissions to SATs. In How Children Succeed, Paul Tough argues that success has more to do with character??―??skills like perseverance, curiosity, optimism, and self-control. In this groundbreaking study, Tough introduces us to key researchers and educators, who, for the first time, are using the tools of science to peel back the mysteries of character. Through their stories??―??and the stories of the children they are trying to help??―??Tough reveals how character has the power to transform young people?s lives. This provocative and profoundly hopeful book will not only inspire and engage readers??―??it will also change our understanding of childhood itself.
Includes bibliographical references and index.
Keywords: Success in children; Personality and cognition; Personality and motivation; Personality and academic achievement; Determination (Personality trait) in children